Meningitis in the Setting of Frontoethmoidal and Temporal Meningoencephaloceles. (April 2021) - Kumar, Arooshi; Shah, Jugal; Melmed, Kara; Pacione, Donato; Lieberman, Seth; Lewis, Ariane
This is a patient with multiple meningoencephaloceles which resulted in bacterial meningitis and subsequent status epilepticus. We identify impressive imaging findings demonstrating herniation of the meninges from nasal and bitemporal skull base defects possibly as a result of intracranial hypertension.